2020
DOI: 10.3390/pathogens9030162
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Haemonchus contortus Excretory/Secretory Antigen (ES-15) and Its Modulatory Functions on Goat Immune Cells In Vitro

Abstract: Small size excretory/secretory (ES) antigens of the Haemonchus contortus parasite have intense interest among researchers for understanding the molecular basis of helminths immune regulation in term of control strategies. Immunomodulatory roles of H. contortus ES-15 kDa (HcES-15) on host immune cells during host–parasite interactions are unknown. In this study, the HcES-15 gene was cloned and expression of recombinant protein (rHcES-15) was induced by isopropyl-ß-d-thiogalactopyranoside (IPTG). Binding activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…NO is considered to be involved in most parasitic infections, mediating the host's non-specific defense by eliminating parasites or delaying parasite growth [ 45 48 ]. Consistent with previous studies [ 47 , 49 , 50 ], this study demonstrated that rBsCPI-1 significantly induces PBMCs to produce NO, which might promote the inflammatory response and pathogenesis during B. schroederi infection.…”
Section: Discussionsupporting
confidence: 92%
“…NO is considered to be involved in most parasitic infections, mediating the host's non-specific defense by eliminating parasites or delaying parasite growth [ 45 48 ]. Consistent with previous studies [ 47 , 49 , 50 ], this study demonstrated that rBsCPI-1 significantly induces PBMCs to produce NO, which might promote the inflammatory response and pathogenesis during B. schroederi infection.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that various HcESP-derived protein molecules, such as rHcMTF-12 [ 54 ], rHCRD [ 37 ], rHc-GDC [ 40 ], rHcEF-1α [ 46 ], rHcES-15 [ 34 ], rMiro-1 [ 55 ], HCcyst-3 [ 56 ] and RHC-AK [ 57 ], can bind to PBMCs in vitro and regulate cellular immune function. Our studies showed that rHcGOB can bind to goat PBMCs and activate the IL-10/TGF-β/STAT3 pathway in PBMCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Adult H. contortus worms were obtained as previously described [ 33 ]. Total RNA was extracted from adult worms by the TRIzol reagent (Invitrogen, Carlsbad, CA, USA) method [ 34 ]. The complementary DNA (cDNA) was synthesized by HiScript III Kit (Vazyme, Nanjing, China) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…H. contortus complementary DNA (cDNA) was synthesized as previously described ( 28 ). The 160–702-aa region of the glycosyltransferase domain-containing protein (GenBank: HF965754.1) is the 6-phosphorylase synthase structural domain (Hc-TPS).…”
Section: Methodsmentioning
confidence: 99%